Effect of Dexmedetomidine Nebulization on the Hemodynamic Parameters during Laryngoscopy and Endotracheal Intubation - Prasai, Adim; Prasai, Abha (Nepal Medical College Journal, 2025)
Dexmedetomidine is an alpha-2 agonist used to attenuate the hemodynamic response to laryngoscopy and endotracheal intubation via the intravenous route. Our study was performed in 390 patients undergoing general anesthesia to assess the effect of dexmedetomidine nebulization on the hemodynamic parameters during laryngoscopy and endotracheal intubation. Group D received 0.75 mcg/kg dexmedetomidine diluted in 0.9% normal saline and group S received 3 ml of normal saline 30 minutes before induction of anesthesia. After laryngoscopy and intubation there was significantly lower trend of increase in heart rate and systolic blood pressure in group D (p<0.001) at 2, 4 and 6 minutes. Similarly, there was lower trend of increase in diastolic blood pressure and mean arterial pressure in 2, 4 ,6, 8 and 10 minutes (p <0.001). Dexmedetomidine by nebulization route attenuated the increase HR, SBP, DBP and MAP after laryngoscopy and endotracheal intubation. There was a reduction in intraoperative anesthetic and analgesic use. There was no increase in the incidence of adverse effects such as hypotension and bradycardia. Nebulized dexmedetomidine may be used for stabilization of hemodynamic parameters during laryngoscopy and endotracheal intubation.